Analysis Study of Boarding Schools Management In Implementing Religious Moderation Values - Muhammad Alfian; Rian Anugrah Firmanto; Muhammad Rifai (International Journal of Education, Vocational and Social Science, 2022)
Since the first, the true character of the pesantren is multicultural. This is deemed necessary due to the categorization or grouping that has occurred to date between traditional Islam and modern Islam, and within certain limits, due to conflicts between Islamic teachings (brought by traders and preachers from the Middle East) and Christian teachings (which brought by traders and missionaries from the Netherlands). Pesantren was established before the Republic of Indonesia was founded, so it is an education that is deeply rooted in society. The students also come from various cultural backgrounds. Sometimes there is a pesantren whose students come from dozens of provinces, which means that pesantren are in demand across cultures. This is important in relation to religious moderation. Religious moderation in Islamic boarding schools, if summarized, is contained in several principles that become the guidance of the santri. This is what the Ministry of Religion continuously socializes so that it becomes the main stream in social and national life.